1, 25(OH)2D3 inhibited Th17 cells differentiation via regulating the NF‐κB activity and expression of IL‐17. (24th April 2018) - Sun, Dong; Luo, Fei; Xing, Jun‐chao; Zhang, Fei; Xu, Jian‐zhong; Zhang, Ze‐hua
Abstract: Objectives: The role of vitamin D (VD) in innate and adaptive immune responses to tuberculosis is still unclear. Our research was aimed to uncover the effect of VD on Th17 cells and elucidate potential molecular mechanism. Materials and methods: VDR‐deficient and wild‐type mice were used to obtain CD4 T cells. Th17 cells were induced and activated by Bacillus Calmette Guerin. Flow cytometry was used to analyse the apoptosis rate and degree of differentiation of Th17 cells in the treatment of 1, 25(OH)2 D3 . The interaction between P65 and Rorc was determined by immunofluorescence assay, luciferase reporter assay, EMSA‐Super‐shelf assay and ChIP assay. Co‐IP assay was carried out to test the interaction between VDR and NF‐κB family proteins. qRT‐PCR and Western blot were also performed to detect the levels of P65, RORγt and IL‐17. Results: The Th17 cells differentiation was suppressed by 1, 25(OH)2 D3 in vitro. We confirmed that Rorc was a downstream gene of the transcription factor P65. VDR interacts with P105/P50, P100/P52 and P65 NF‐κB family proteins. 1, 25(OH)2 D3 inhibited the expression of RORγt/IL‐17 by suppressing p65 transcription factor translocating to nucleus. In vivo experiments, the expression of IL‐17 and RANKL was suppressed by 1, 25(OH)2 D3 by VD receptor. Moreover, 1, 25(OH)2 D3 suppressed the inflammatory infiltrates and inhibited the expression of P65, RORγt and IL‐17 in the spleen tissues of model mice. Conclusions: Together, 1, 25(OH)2 D3 suppressed the differentiation of Th17 cells via regulating the NF‐κB activity.